Bargained Wages, Wage Drift and the Design of the Wage Setting System - Ana Rute Cardoso; Pedro Portugal (Institute for the Study of Labor (IZA), 2003)
This paper aims at answering the question: How does a typically 'European' bargaining system - with collective bargaining, extension mechanisms and national minimum wage - coexist with low unemployment rate and high wage flexibility? A unique data set on workers, firms and collective bargaining contracts in the Portuguese economy is used to analyze the determinants of both the bargained wage and the wage drift. Results indicate that wage drift stretches the returns to every worker and firm attribute, whereas it shrinks the returns to union bargaining power. Therefore, firm-specific arrangements, in the form of wage drift, partly offset collective bargaining, granting firms a high degree of freedom when setting wages. Union bargaining power raises the overall wage level, but lowers the returns on worker attributes, an outcome of the egalitarian policy pursued.
Keywords: J51; J31; D21; 330; wage distribution; wage drift; union bargaining power; employer coordination; Tarifpolitik; Lohnverhandlungen; Lohndrift; Arbeitsmarktflexibilisierung; Schätzung; Portugal